How Property Shapes Distributional Preferences - Marco Fabbri; Maria Bigoni (Institute of Labor Economics (IZA), 2021)
We study how distributional preferences are affected by a major property rights reform that transformed informal use-rights over land traditionally characterizing rural Beninese villages in a system akin to private ownership. The design combines the randomized control-trial implementation of the reform across villages with lab-in-the-field experiments eliciting villagers' distributional choices – both when luck is the source of situational inequality and when an unequal distribution is originated by merit considerations. Results show that reforming allocation rules in the direction of impersonal market-alike institutions increases participants' acceptance of inequality determined by luck, while leaving participants' tolerance for inequality generated by merit unaffected.
Keywords: D31; C93; D01; 330; fairness; institutional change; lab-in-the-field experiment; land tenure reform; land titling